(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article investigates the effectiveness of psychological incentive methods for boosting trainee motivation during military training. It first explores the theoretical foundations of motivation in military preparedness and the key factors shaping it. The study then examines social-psychological incentives (positive competition within the unit, collective achievement recognition), emotional-psychological incentives (praise, symbolic rewards, acknowledgment of personal growth), and cognitive-psychological incentives (goal-setting techniques, self-reflection, task meaningfulness). An experimental study conducted with cadets of the Academy under Uzbekistan’s Ministry of Defense showed that combining these methods increased intrinsic motivation by 23 % and extrinsic motivation by 17 %. The frequency of moral-ethical support, the individually calibrated difficulty of tasks, and the cooperative style of instructors were found to correlate directly with overall motivation levels. Practical recommendations are provided on integrating psychological incentives into training content to sustain high motivation, thereby improving training efficiency and strengthening cadets’ combat readiness.